Die gesprek tussen AB du Toit en EP Sanders oor Paulus en die Palestynse Judaisme: Die pad vorentoe - Craffert, P. F. (Hervormde teologiese studies, 1989)
The debate between AB du Toit and EP Sanders on Paul and Palestinian Judaism: The road ahead The aim of the article is to analyse the underlying structure of the critical reaction of AB du Toit against EP Sanders’s Pauline interpretation. It is shown that Du Toit’s criticism of Sanders rests on his identification of Paul’s opponents and their theology in Romans 4. This is questioned because of the dubious grounds on which his argument rests: the antithesis which is interpreted as polemical and the use of mirror reading. Secondly the underlying structures of their arguments are analysed. From this it becomes clear that there are hermeneutical and methodological differences between them which prevents Du Toit to do justice to Sanders’s interpretation. Lastly it is suggested that a movement away from a strictly ‘theological approach ’ to one which also takes the social context seriously, may be of much help in understanding what the historical Paul was saying.